Fluorescence in Industry - Pedras, Bruno (Springer Series on Fluorescence, Methods and Applications, 2019)
This book gathers 12 outstanding contributions that reflect state-of-the-art industrial applications of fluorescence, ranging from the pharmaceutical and cosmetics industries to explosives detection, aeronautics, instrumentation development, lighting, photovoltaics, water treatment and much more. In the field of fluorescence, the translation of research into important applications has expanded significantly over the past few decades. The 18th volume in the Springer Series on Fluorescence fills an important gap by focusing on selected industrial applications of fluorescence, described in contributions by both industry-based researchers and academics engaged in collaborations with industrial partners. .